Proceedings of the 9th International Symposium on Networks-on-Chip 2015
DOI: 10.1145/2786572.2788711
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Wireless Network-on-Chip with a Dynamic Medium Access Mechanism

Abstract: Wireless interconnects have emerged as an energy-efficient interconnection paradigm for multicore chips with Networks-onChips (NoCs). As wireless interconnects have the unique advantage of eliminating the need to layout physical channels they provide an inherent opportunity for dynamic reconfiguration of the NoC architecture. Large temporal and spatial variability in traffic patterns is expected in large multicore chips and especially in future heterogeneous systems-on-chips integrating different kinds of core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
(41 reference statements)
0
20
0
Order By: Relevance
“…Physical Constraints [1], [5], [6], [9], [ [8] by implementing both token passing and CSMA and designing a controller that dynamically switches between both strategies depending on the load. A step further towards this direction would be the use of protocols that naturally and gradually adapt their characteristics to the load without the need of an external controller.…”
Section: Conventional Wireless Networkmentioning
confidence: 99%
“…Physical Constraints [1], [5], [6], [9], [ [8] by implementing both token passing and CSMA and designing a controller that dynamically switches between both strategies depending on the load. A step further towards this direction would be the use of protocols that naturally and gradually adapt their characteristics to the load without the need of an external controller.…”
Section: Conventional Wireless Networkmentioning
confidence: 99%
“…The work in [56] proposes a slotted CSMA scheme with theoretically optimal persistence calculated a priori, and compares its performance with that of a token passing scheme. Given that these protocols perform better for different loads, the authors of [57] propose a scheme that dynamically switches between both depending on communication intensity.…”
Section: Mac: Medium Access Control In Wnocmentioning
confidence: 99%
“…Dai et al propose the use of slotted Carrier Sense Multiple Access (CSMA) with optimal persistence calculated a priori [6]. Also, Mansoor et al present an adaptive scheme that switches between CSMA and token passing depending on the level of contention [14]. These works show novelty, but do not detail how would multicasts be acknowledged or how the protocol scales.…”
Section: Broadcast-oriented Wireless Network-on-chipmentioning
confidence: 99%
“…In this paper, we focus on the MAC issue and propose BRS-MAC, a protocol specifically suited to the broadcastoriented WNoCs. We observed that existing works on WNoC either rely on channelization or token passing schemes that do not scale well [7,9], or map protocols to the on-chip scenario without considering broadcast patterns [6,14]. Instead, our work takes advantage of the unique application context to propose a scalable and reliable solution, as well as to develop highly accurate performance models.…”
Section: Introductionmentioning
confidence: 99%